Modeling and design of a high efficiency hybrid heat pump clothes dryer. (September 2017) - TeGrotenhuis, Ward; Butterfield, Andrew; Caldwell, Dustin; Crook, Alexander; Winkelman, Austin
Abstract: Computational modeling is used to design a hybrid heat pump clothes dryer capable of saving 50% of the energy used by residential clothes dryers with comparable drying times. The model represents the various stages of a drying cycle from warm-up through constant drying rate and falling drying rate phases and finishing with a cooldown phase. The model is fit to data acquired from a commercially available U.S. standard vented electric clothes dryer, and when a hybrid heat pump system is added, the energy factor increases from 3.0 lbs/kWh to 5.7–6.0 lbs/kWh, depending on the increase in blower motor power. The hybrid heat pump system is designed from off-the-shelf components and includes a recuperative heat exchanger, an electric element, and an R-134a vapor compression heat pump. Parametric studies of element power and heating element use show a trade-off between energy savings and cycle time. Results show a step-change in energy savings from heat pump dryers currently marketed in the U.S. based on performance represented by Energy Star from standardized DOE testing.